Factors affecting Malaysian behavioral intention to adopt mobile wallet - Ding, Ying Tsyr; Lim, Fei Ming (2018)
The primary objective of this research is to determine the factors that affect Malaysian’s behavioral intention to adopt mobile wallet. This research is to investigate the relationship of perceive ease of use, perceived usefulness, perceived risk between consumer attitudes and behavioral intention and to test the role of consumer attitudes as a mediator between perceived risk and behavioral intention. The target respondents of this study are Malaysian who does not use mobile wallet before and intend to use it in future. In addition, 300 sets of questionnaire were distributed through hard copy by using convenient sampling and snowball sampling technique. However, only 233 sets of questionnaire are valid to use in this research. The actual data collected will be analyzed using Statistical Package for Social Science (SPSS) version 23. Then, Internal Reliability Test, Multiple Regression Analysis and mediated variable regression are conducted. In this research, result shows that independent variables which are perceived ease of use and perceived usefulness have significant positive relationship with attitude, while, attitude also has positive relationship with behavioral intention. On the other hand, attitude as a mediator between perceived risk and behavioral intention has result as partial mediate. However, perceived risk has no impact towards attitude. Moreover, this research provides a clearer overview for academicians, developers and users who currently involved in mobile wallet. Lastly, the limitations associated with this research project were identified and implications for further research were recommended.